The Share Price Behavior of the IPO Surrounding the Expiration of the Lockup Period. Evidence from IPOs with No Analyst Positive Recommendations - Azlan, Md Thani; Muhammad Mukhlis, Abdul Fatah; Shazali, Shaharudin; Mohd Ariff, Mustafa; Mohd Waliuddin, Mohd Razali (IMBR publishes, 2024)
This study investigates the share price performance of the IPOs surrounding the expiration of the lockup period in the Malaysian stock market. The study explores whether the IPOs without analysts’ positive recommendations give a significant positive share price performance in situations of the negative effect of the expiration of the lockup period. The IPOs sample of 281 companies was taken from the period of January 2000toDecember 2014. The study applied event study methodology to investigate the performance of the IPO share price. The study found that the IPOs without analysts’ positive recommendations gave an insignificant positive share price performance in the event window of (-10, +10) surrounding the expiration of the lockup period. Whilst, the longer event window (-30, +30) shows a significant positive share price performance surrounding the expiration of the lock-up period